2017
DOI: 10.1091/mbc.e17-04-0253
|View full text |Cite
|
Sign up to set email alerts
|

Active Ran regulates anillin function during cytokinesis

Abstract: We describe a novel mechanism by which active Ran regulates anillin during cytokinesis. Anillin is highly conserved and coordinates RhoA, actomyosin, microtubules, and the membrane for cytokinesis in mammalian cells. This study implicates Ran-GTP in influencing cortical contractility during anaphase by regulating anillin function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 52 publications
3
68
0
2
Order By: Relevance
“…We found the NLS of anillin is required for its localization and function during cytokinesis (Beaudet et al, 2017). In addition, anillin contains a RhoA-binding domain (RBD) required for cortical recruitment, and we found that the RBD autoinhibits the adjacent NLS-containing C2 domain.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…We found the NLS of anillin is required for its localization and function during cytokinesis (Beaudet et al, 2017). In addition, anillin contains a RhoA-binding domain (RBD) required for cortical recruitment, and we found that the RBD autoinhibits the adjacent NLS-containing C2 domain.…”
Section: Introductionmentioning
confidence: 82%
“…Since anillin crosslinks key components of the cell during cytokinesis, understanding its molecular regulation can provide insight to how cytokinesis is regulated. In particular, the C-terminus of anillin contains a RhoA-GTP binding domain (RBD), a neighboring C2 domain, and a Pleckstrin Homology (PH) domain, which coordinate its localization through 1) binding to active RhoA, 2) binding to phospholipids, importins and/or microtubules via the C2 domain, and 3) binding to phospholipids and/or septins via the PH domain (Oegema et al, 2000;Piekny and Glotzer, 2008;Piekny and Maddox, 2010;Liu et al, 2012;van Oostende Triplet et al, 2014;Sun et al, 2015;Beaudet et al, 2017). However, which of these interactions is crucial for anillin function and how they are coordinated is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ANLN , a conserved multi‐domain protein, is a prime candidate for functioning in scaffolding and organizing the cytoskeleton due to its many protein–protein interactions. In humans, ANLN is required for cortical polarity and cytokinesis (Beaudet, Akhshi, Phillipp, Law, & Piekny, ). Considering that human ANLN is normally degraded after mitotic exit and sequestered in the nucleus during interphase, its over‐expression may disturb these normal regulatory mechanisms, freeing ANLN to affect the actomyosin cytoskeleton during events outside of cytokinesis, including, cell motility which promotes cell differentiation and the spatial programing of the inner, middle and outer structures of the ears (Noden & Van de Water, ; Zhang & Maddox, ).…”
Section: Discussionmentioning
confidence: 99%